2019
DOI: 10.24843/eja.2019.v28.i01.p25
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Profitabilitas, Struktur Aset, Likuiditas, Dan Pertumbuhan Penjualan Terhadap Struktur Modal Perusahaan Makanan Dan Minuman

Abstract: The purpose of this research is to understand the effect of profitability, asset structure, liquidity, and sales growth on the capital structure of food and beverage companies listed on the IDX. This research was conducted at 19 food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017 by accessing the website www.idx.co.id. The sample used in this study was determined using a non probability sampling method by used purposive sampling technique, so the final sample used in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 1 publication
2
7
0
6
Order By: Relevance
“…Based on this description, it can be concluded that the higher the growth rate of the company, the higher the level of debt utilization by the company. This statement is strengthened by an empirical study of the effect of sales growth on capital structure as conducted by (Gunadhi & Putra, 2019) which shows that sales growth has a positive effect on capital structure. Based on a number of supporting results, the following hypothesis is formulated: H3: Sales growth affects the capital structure.…”
Section: The Effect Of Sales Growth (X3) On Capital Structurementioning
confidence: 98%
See 1 more Smart Citation
“…Based on this description, it can be concluded that the higher the growth rate of the company, the higher the level of debt utilization by the company. This statement is strengthened by an empirical study of the effect of sales growth on capital structure as conducted by (Gunadhi & Putra, 2019) which shows that sales growth has a positive effect on capital structure. Based on a number of supporting results, the following hypothesis is formulated: H3: Sales growth affects the capital structure.…”
Section: The Effect Of Sales Growth (X3) On Capital Structurementioning
confidence: 98%
“…The company's capital structure will change depending on the development of the company's sales level. Previous empirical evidence (Gunadhi & Putra, 2019) states that the results of Sales Growth have a positive effect on capital structure, while the results of research conducted by (Yudiandari, 2018) show that the results of Sales Growth have a negative effect on capital structure. And (Wijaya & Utama, 2014) show that sales growth results have no effect on capital structure.…”
Section: Introductionmentioning
confidence: 95%
“…Dengan adanya aset atau aktiva yang besar apabila perusahaan lalai dalam pembayaran hutangnya maka asset tersebut dapat mejadikan jaminan bagi kreditur. Dari hasil penelitian (Gunadhi & Putra, 2019) dan (Ahmad, 2017) menunjukan struktur aset memiliki pengaruh positif signifikan terhadap struktur modal. Sementara itu, berdasarkan penelitian (Tiara & Isnurhadi, 2018) dan (Dewi & Fachrurrozie, 2021) membuktikan struktur aset memiliki pengaruh negatif signifikan terhadap struktur modal.…”
Section: Pendahuluanunclassified
“…Jadi inilah yang membuat hubungan negatif antara likuiditas dan struktur modal. Penelitian ini mendukung temuan sebelumnya dari (Umam & Mahfud, 2016) dan (Gunadhi & Putra, 2019) bahwa likuiditas memiliki pengaruh negatif dan signifikan terhadap struktur modal.…”
Section: Non-debt Tax Shieldunclassified
See 1 more Smart Citation